Sunsets, seafood and sea gypsies: A qualitative content analysis on the alternative destination image of Malaysian Borneo among Chinese outbound tourists - Ke Zhang; Balvinder Kaur Kler; Siao Fui Wong (ResearchGate, 2024)
The purpose of this work is to explore the online destination image perceived by Chinese tourists visiting Sabah, Malaysian Borneo. Employing Leiper’s tourism system as a guiding framework, the research utilized qualitative content analysis (QCA) to scrutinize a purposefully selected sample of thirty-seven Douyin contents, which is known outside China as TikTok. Findings indicate an alternative destination image, with Chinese tourists highlighting sunsets, seafood and sea gypsies as prominent attributes, deviating from the conventional association of sun, sea and sand. This distinctive perception contrasts with the perceptions held by Western tourists of Sabah. Informed by Leiper’s tourism system, this study emphasizes the importance for coastal destination marketing organizations to convey a destination image that extends beyond the conventional sun-sea-sand concept. Effective communication requires a nuanced understanding of unique destination images tailored to specific market segments based on their respective tourist generating regions. This approach aligns with Leiper’s emphasis on the interconnected relationships between the tourist generating region and the tourist destination region, providing insights for strategic destination marketing that cater to diverse tourist perspectives. The findings interpret user-generated content (UGC) within Leiper’s tourism system, consolidating the importance of projected online destination images.